The response to sulpiride in social anxiety disorder: D2 receptor function. (February 2013) - Bell, Caroline; Bhikha, Shamina; Colhoun, Helen; Carter, Frances; Frampton, Chris; Porter, Richard
Some previous studies have suggested that patients with social anxiety disorder (SAD) have a hypoactive central dopaminergic system. Supporting this there have been reports from neuroimaging studies of reduced striatal D2 receptor binding in subjects with SAD. The aim of this study was to investigate D2 receptor sensitivity in patients with SAD compared with a group of matched, healthy controls using a neuroendocrine challenge with the selective D2 antagonist, sulpiride. D2 receptor function was assessed in 23 subjects with generalized SAD and 23 matched, healthy controls using a challenge with 400 mg of a selective D2 antagonist, sulpiride in a randomized, placebo-controlled, crossover design. Response to sulpiride was measured by the change in prolactin level and changes in self-rated measures of social anxiety, mood and the ability to experience pleasure. There was no significant difference in prolactin response to sulpiride between the two groups. Sulpiride resulted in no effect in either the SAD or healthy control group on measures of social anxiety, mood or the ability to experience pleasure. Contrary to our hypothesis, in this study we found no evidence of reduced D2 receptor function in subjects with SAD compared with healthy controls.